Assisting with patient care workbook - Sorrentino, A. Sheila (St. Louis, Mo. : Mosby, 2004)
This comprehensive chapter-by-chapter companion to the textbook (Assisting with Patient Care, 2nd edition, by Sheila Sorrentino, ISBN 0323024963) includes a wide variety of exercises to enhance learning and hold students' interest. Covers all basic concerns and skills needed by Nursing Assistants.
"Assisting With Patient Care Workbook, 2nd edition, is to be used with Mosby's textbook, Assisting With Patient Care, 2nd edition, by Sheila A. Sorrentino."--Pre.